PERAN HUKUM DALAM PLATFORM E-COMMERCE DALAM ERA TRANSFORMASI DIGITAL DI DESA BATUNUNGGAL KECAMATAN CIBADAK KABUPATEN SUKABUMI - Ginanjar, Heri; Septiana, Tina; Rosmiati, Neni; Nurhalimah, Siti; Taufik, Tata Muhammad; Suci, Nabila Thalita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This community service aims to improve the understanding and implementation of legal aspects in e-commerce platforms in the era of digital transformation in Batununggal Village, Cibadak District, Sukabumi Regency. The program was implemented through a workshop method with a participatory approach, involving 20 MSME players. The result was 30% who have utilized the e-commerce platform and 85% admitted to have a limited understanding of the legal aspects of electronic transactions. The program also resulted in the establishment of a digital business community and a digital legal consultation center at the village level. The sustainability of the program is supported through an ongoing mentoring system and the development of an online learning module